GROWTH AND DEVELOPMENT OF SOYBEAN DEPENDING ON SOWING TIME AND MICROBIOREACTOR - Кулібаба, М. Ю. (Scientific Progress & Innovations, 2015)
The duration of the vegetation period of the plants of soybean depends on sowing time: the longest it at early period, and under optimal and late it decreases. The duration of the interphase periods during the growing season was also distributing differently depending on sowing time. The degree of development of plants during the growing season depends on pre-treatment of seeds of microbiological preparations: plants which at the sowing day were treated by drug «Rizogumin» develop better at all three rows of planting. However, yield and it’s quality depends on the processing of biological preparations and sowing dates. The highest rates were observed in plots treated with «Rizogumin» which were sown in early term.